EFFICIENCY OF RAW MATERIAL INVENTORIES IN IMPROVING SUPPLY CHAIN PERFORMANCE of CV. FIVA FOOD - Artadi Nugraha; Sukardi Sukardi; Amzul Rifin (School of Business, IPB University (SB-IPB), 2016)
The production and number of processed food industries have slightly increased; as a result, the companies must compete to maximize their profits by conducting their efficient production process. CV. Fiva Food is one of the companies in the field of processed foods, especially in processed meat that has implemented supply chain management. It is necessary for the company to take measurements of its performance and efficiency for the entire supply chain such as procurement of raw materials. The purposes of this study were to analyze the performance of the company's supply chain and determine the most efficient method of procurement for its raw materials as well as and to provide recommendations for the company to improve its performance of entire supply chain. This study used SCOR in analyzing the performance of supply chain and EOQ and POQ method to be compared with the method that the company uses to determine which method of procurement for raw materials is the most efficient one. The result showed that based on the matrix, the company's performance is unfavorable when it was compared to the benchmark performance of inventory days of supply. In addition, this study showed that the POQ method produces the lowest total inventory cost with savings of Rp6.647.015 for raw materials of MDM whereas EOQ method produced the lowest total inventory cost with savings of Rp222.153,78 for raw materials of FQ85CL. Keywords: performance suppy chain, SCOR, fiva food, EOQ, POQ